One vote away : how a single Supreme Court seat can change history - Cruz, Ted, 1970- (Regnery Publishing ; a division of Salem Media Group, 2020)
Senator Cruz argues that the high court decisions that affect your life have been decided by just one vote. Case studies illustrate his point that one vote preserves your right to speak freely, to bear arms, and to exercise your faith.